Clusia mocopetraea, a rupicolous new species of Clusiaceae from Serra do Cabral, Minas Gerais, Brazil - Alencar, Ana Cláudia; Nascimento-Jr, José Elvino Do; Bittrich, Volker; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2026)
Serra do Cabral is an isolated massif in north-central Minas Gerais, part of the Espinhaço Range, a region renowned for its high biodiversity and endemism in Brazil. The predominant vegetation belongs to the Cerrado domain, especially rocky outcrop ecosystems. Recent fieldwork led to the discovery of a new Clusia (Clusiaceae) species, morphologically similar to C. diamantina. Based on morphological analyses and ecological niche modelling, we here describe and illustrate this new species, highlighting the importance of the Serra do Cabral as a centre of diversity and a priority area for the conservation of Neotropical flora.